The Dunhuang Grottoes and global education: philosophical, spiritual, scientific, and aesthetic insights - Xu, Di (Spirituality, religion, and education, 2019)
Introduction : Dunhuang and education--the missing piece / Xu Di -- Dunhuang's infinite connections with education / Xu Di, Leng Lu -- Educational philosophy and Dunhuang : diversity, synergy, and transformation / Xu Di -- Moral education from the Dunhuang murals / Chia-Ling Wang -- The philosophy of aesthetic education in Ch'an Buddhism : a new interpretation of the Mandala Sutra of the sixth patriarch from Dunhuang / Kang Lee -- West meets east : the interplay of unity and diversity--the relevance of Dunhuang for education and life today / Xu Di -- Enlightenment from body-spirit integration : Dunhuang's Buddhist cultivation pathways and educational applications / Jing Lin -- Dunhuang as a model for EthnoSTEM education / Rui Kang, Joseph Peters -- The significance of the Dunhuang Mogao frescoes for universal education today / Su Xiaojia, Zhou Hongtao -- A psychological perspective of Dunhuang education : heart, soul, and our lives / Leng Lu -- Dunhuang and contemporary music education / Yu Danhong -- The textbooks of basic Dunhuang education : implications for teaching and learning / Leng Lu -- Dunhuang and lifelong learning in the global context / Zhang Jianhui -- Harmonious coexistence with nature : naturalistic education in the Dunhuang frescoes / Song Baoru.